Isocaloric intake of a high‐fat diet promotes insulin resistance and inflammation in Wistar rats. (24th September 2012) - Jacob, Patrícia Silva; de, Tatiane Mieko; Yamada, Monica; Borges, Maria Carolina; Pantaleão, Lucas Carminatti; Borelli, Primavera; Fock, Ricardo; Rogero, Marcelo Macedo
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate the effect of isocaloric intake from a high‐fat diet (HFD) on insulin resistance and inflammation in rats. Male Wistar rats were fed on an HFD (n = 12) or control diet (n = 12) for 12 weeks. Subsequently, all animals were euthanized, and blood glucose, insulin, free fatty acids, C‐reactive protein, lipid profile, cytokines and hepatic‐enzyme activity were determined. Carcass chemical composition was also analyzed. During the first and the twelfth weeks of the experimental protocol, the oral glucose tolerance test and insulin tolerance test were performed and demonstrated insulin resistance (P < 0.05) in the HFD group. Although food intake (g) was lower (P < 0.05) in the HFD group compared with the control group, the concentration of total cholesterol, low‐density lipoprotein, C‐reactive protein and liver weight were all significantly higher. The kinase inhibitor of κB, c‐Jun N‐terminal kinase and protein kinase B expressions were determined in the liver and skeletal muscle. After an insulin stimulus, the HFD group demonstrated decreased (P = 0.05) hepatic protein kinase B expression, whereas the kinase inhibitor of κB phospho/total ratio was elevated in the HFD muscle (P = 0.02). In conclusion, the isocaloric intake from the HFD induced insulin resistance, associated with impaired insulin signalling in the liver and an inflammatory response in the muscle. Copyright © 2012 John Wiley & Sons, Ltd.